Coronary calcium scoring from contrast coronary CT angiography using a semiautomated standardized method - Schuhbaeck, Annika; Otaki, Yuka; Achenbach, Stephan; Schneider, Christian; Slomka, Piotr; Berman, Daniel S.; Dey, Damini (Journal of Cardiovascular Computed Tomography, 2015)
When coronary calcium scoring is performed in patients with suspected coronary artery disease, a separate noncontrast scan is acquired before contrast-enhanced coronary CT angiography (CTA).Our aim was to develop and validate an automated method for calculating the coronary calcium score (CCS) from coronary CTA.We analyzed coronary CTA and noncontrast CT data sets of 84 patients (Agatston score >0). The CCS on noncontrast CT was measured using commercial methods. Coronary calcium volume was measured on coronary CTA using an automated standardized method with scan-specific calcium thresholds. Data sets were split into derivation (n = 40) and validation groups (n = 44). To calculate the CCS on coronary CTA, a conversion factor between calcium scores measured in noncontrast CT and the calcium volume measured on coronary CTA was derived by linear regression.In the validation group, the median calculated CCS derived from CTA was 277 and 244 on noncontrast images (P = .12). This CCS showed an excellent correlation with the CCS from noncontrast images (Pearson, r = 0.95). In the validation group, 39 of 44 patients (88.6%) were classified into the same standard category (1-10, 11-100, 101-400, or >400) with an excellent agreement (weighted ? of 0.87).CCSs can be accurately measured from contrast-enhanced coronary CTA by using an automated, standardized method, obviating the need for a noncontrast scan.
EVALuna2:12081